Ch. Chhotu Ram: A Great Reformer: The Contributions and Reforms of Ch. Chhotu Ram (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Ch. Chhotu Ram joined the All India Congress party in 1916. He played a major role as the president of rohtak distt. Congress committee. He was the ‘MASIHA’ of oppressed community. .When he became a minister of Punjab govt. he passed a lot of acts to improve the condition of peasant class. Punjab agriculture produce marketing act, Punjab sugarcane act, Bakhra dam project was major acts which was passed only by the efforts of ch. Chhotu ram. Two canals in rohtak and hisar district was very great contribution in the irrigation of Haryana. He was an active supporter of Arya Samaj which was a great socio-religious reform movement at that time. He emphasized on opening school in rural areas.